Paper Microfluidics for Cell Analysis. Issue 1 (26th November 2018) - Ma, Jun; Yan, Shiqiang; Miao, Chunyue; Li, Linmei; Shi, Weiwei; Liu, Xianming; Luo, Yong; Liu, Tingjiao; Lin, Bingcheng; Wu, Wenming; Lu, Yao
Abstract: Paper microfluidics has attracted much attention since its first introduction around one decade ago due to the merits such as low cost, ease of fabrication and operation, portability, and facile integration with other devices. The dominant application for paper microfluidics still lies in point‐of‐care testing (POCT), which holds great promise to provide diagnostic tools to meet the ASSURED criteria. With micro/nanostructures inside, paper substrates provide a natural 3D scaffold to mimic native cellular microenvironments and create excellent biointerfaces for cell analysis applications, such as long‐term 3D cell culture, cell capture/phenotyping, and cell‐related biochemical analysis (small molecules, protein DNA, etc.). This review summarizes cell‐related applications based on various engineered paper microdevices and provides some perspectives for paper microfluidics‐based cell analysis. Abstract : Paper microfluidics has attracted much attention since its introduction around one decade ago due to the merits such as low lost, ease of fabrication and operation, portability, and facile integration with other devices. This review summarizes cell analysis applications based on various paper microdevices, such as 3D cell culture, cell capture/phenotyping, and cell‐related biochemical analysis (small molecules, protein, DNA, etc.).